The Cambridge companion to pragmatism - Malachowski, Alan R. (Cambridge : Cambridge University Press, 2013)
'Pragmatism established a philosophical presence over a century ago through the work of Charles Peirce, William James and John Dewey, and has enjoyed an unprecedented revival in recent years owing to the pioneering efforts of Richard Rorty and Hilary Putnam. The essays in this volume explore the history and themes of classic pragmatism, discuss the revival of pragmatism and show how it engages with a range of areas of inquiry including politics, law, education, aesthetics, religion and feminism. Together they provide readers with an overview of the richness and vitality of pragmatist thinking and the influence that it continues to exert both in philosophy and other disciplines. The volume will be of interest to students and scholars of pragmatism, American philosophy and political theory'--
Includes bibliographical references (pages 345-366) and index.
Keywords: Pragmatism